التعليم عن بعد في الجامعات الجزائرية - دهيمي,زينب; جلال,إبراهيم (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى تحليل تأثير التعليم عن بُعد على جودة التعليم في الجامعات الجزائرية، خاصة في ظل التحديات التي واجهت المؤسسات التعليمية خلال جائحة كوفيد-19، تم التركيز على كيفية تأثير هذا النمط التعليمي على الأداء الأكاديمي للطلاب، جودة التدريس، ورضا الطلاب وأعضاء هيئة التدريس لتحقيق نتائج أفضل، توصي الدراسة بضرورة تحسين البنية التحتية الرقمية في الجامعات، تدريب الأساتذة والطلاب على استخدام تقنيات التعليم عن بُعد، وتطوير سياسات أكثر فعالية لتقييم الأداء الأكاديمي بشكل يتماشى مع هذا النمط من التعليم تخلص الدراسة إلى أن التعليم عن بُعد في الجزائر يمتلك إمكانيات كبيرة لتحسين جودة التعليم في المستقبل، لكنه يحتاج إلى تعزيز القدرات التقنية والبشرية لتحقيق أقصى استفادة منه. Study Summary: This study aims to analyze the impact of distance education on the quality of education in Algerian universities, especially in light of the challenges faced by educational institutions during the Covid-19 pandemic The focus was on how this educational style affects students' academic performance, teaching quality, and student and faculty satisfaction to achieve better results The study recommends the need to improve the digital infrastructure in universities, train professors and students to use distance education technologies, and develop more effective policies to evaluate academic performance in line with this style of education The study concludes that distance education in Algeria has great potential to improve the quality of education in the future, but it needs to enhance technical and human capabilities to make the most of it.
أثره على الجودة التعليمية والتحديات المستقبلية
Keywords: التعليم عن بعد; جودة التعليم; Distance education; Quality of education